Struktur Biaya dan Profitabilitas Usaha Tani Kacang Tanah di Desa Pulahenti Kecamatan Sumalata Kabupaten Gorontalo Utara - Yuriko Boekoesoe; Yanti Saleh (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2015)
This study aims to determine the cost structure of the peanut farm in the village of Pulahenti and to determine the profitability of farming in the village Pulahenti peanuts. The method used in this study is a survey method consists of primary data obtained through interviews with peanut farmers using questionnaires / questionnaire and secondary data obtained from the Office of Rural Pulahenti and BPS. sampling technique is done by using the method of sampling saturated or where all members of a population census respondents sampled farmers. Analysis of the data used is the cost of farming, farm receipts, farm profits, and analysis of R / C ratio. Results of data analysis showed that the cost structure of the peanut farm in the village Pulahenti consisting of a fixed fee that includes the cost of land taxes, depreciation of equipment, and wage labor in the family and the variable costs include the cost of seeds, fertilizers, medicines, and wage labor work outside the family. The average profitability of peanut farm profitability in the Village Pulahenti of Rp. 4.859.992,5/ farmers with the R / C ratio of Rp. 1,86. Based on the criterion value R / C ratio of more than one meaning can be said peanut farm in the village of Pulahenti profitable and worth the effort